2021
DOI: 10.3390/life11080748
|View full text |Cite
|
Sign up to set email alerts
|

Does Needle Design Affect the Regenerative Potential of Bone Marrow Aspirate? An In Vitro Study

Abstract: While autologous bone is still the gold standard for treatment of bone defects, its availability is limited. Sufficient numbers of mesenchymal stroma cells (MSC) may be an alternative. Small volumes of bone marrow aspirate (BMA) were harvested with two different needle systems comparing the yield and regenerative potency of the MSCs. BMA (10 mL) was aspirated from the posterior iliac crest of 12 patients with degenerative spinal disc disease using both needle systems in each patient: the Jamshidi needle (JAM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In particular, the collection of larger bone marrow aspirate volumes with high volume syringes seem to decrease the concentration of BMSCs because of the dilution of the bone marrow sample with peripheral blood [ 49 , 49 ]. The needle used for bone marrow harvesting could be another factor affecting the quality of BMAC and its amount of BMSCs [ 21 , 40 , 42 , 58 ]. Some authors also suggested that a multiple-site harvest can be superior versus a single-site harvest [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the collection of larger bone marrow aspirate volumes with high volume syringes seem to decrease the concentration of BMSCs because of the dilution of the bone marrow sample with peripheral blood [ 49 , 49 ]. The needle used for bone marrow harvesting could be another factor affecting the quality of BMAC and its amount of BMSCs [ 21 , 40 , 42 , 58 ]. Some authors also suggested that a multiple-site harvest can be superior versus a single-site harvest [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are various bone marrow needles available on the market namely (a) Jamshidi needle, (b) Modified Jamshidi needle, (c) Klima sternal needle, (d) Salah bone marrow aspiration needle, (e) Watherfield iliac crest bone marrow aspiration needle, and so on [ 84 ]. Feddahi et al, observed no significant difference regarding the quantity of MNCs and regenerative potency of MNCs in BMAC for either the Jamshidi needle (JAM) on one side and the Marrow Cellution ® Needle (AMC) on the other side when aspirated from the posterior iliac crest of 12 patients [ 101 ]. Oliver et al reported that a slightly higher quantity of MNCs was harvested by multiple-site (31 × 10 6 mL) than single-site (23 × 10 6 mL) bone marrow aspiration using the standard Jamshidi needle whereas a higher quantity of MSCs was retrieved using the single-site method (3486/mL concentrate) than the multiple-site method (2722/mL concentrate) [ 91 ].…”
Section: Variables In the Harvesting And Processing Technique Of Bone...mentioning
confidence: 99%
“…Feddahi et al questions in an in vitro study if the needle design affects the regenerative potential of bone marrow aspirates, which are a promising alternative for the treatment of bone defects [ 5 ]. The authors harvested bone marrow from the posterior iliac crest of 12 patients either with Jamshidi needles or on the contralateral side with Marrow Cellution ® Needles.…”
mentioning
confidence: 99%